Portugal : Request for a Three-Year Arrangement Under the Extended Fund Facility. (IMF Staff Country Reports; Country Report ;, 2011)
Portugal's economy faced severe crisis during the global economic and financial crisis. In this context, Portugal's authorities have put forward an economically well-balanced program that will focus on structural reforms to boost growth and employment, ensure balanced fiscal sustainability, safeguard financial stability, and prevent a credit crunch. The Executive Board of the International Monetary Fund welcomed this step, and approved a three-year arrangement under the Extended Fund Facility for Portugal.